Pembuatan Tepung dari Biji Kakao (Theobroma cacao L) dan Uji Kualitasnya - Asmaul Husna; Suherman Suherman; Siti Nuryanti (Jurnal Akademika Kimia, 2017)
Cacao plant is one of the plantation crops which contribute to improving economic for the Province of Central Sulawesi. This study aimed to prepare and test the flour quality of cocoa beans flour after soaking in salt water, NaCl, and lime water, Ca(OH)2, at various concentrations. Samples were cocoa beans taken from Rantekala Sigi Province of Central Sulawesi, furthermore, the cocoa beans were made into flour. Results showed that the moisture, ash, fat, and carbohydrate of cocoa beans flour were almost met the ISO standard, with the exception of the protein level, i.e 5.0% for max. moisture level, 1.6% for max. ash level, 10.0% for min. fat level, and 70% of min. carbohydrates level. But, the best quality was from soaking with lime water at a concentration of 20% with a value of 2.8% moisture level, at a concentration of 15% with a value of 24.6% level, and at a concentration of 10% with a value of 78.26% carbohydrate level. However, for the ash level, the best quality was by soaking in salt water at a concentration of 5% with a value of 4.1%. Based on these results, it can be concluded that the cocoa beans flour is better soaked in lime water than salt water.